Recursos didáticos, formação inicial docente e o processo de ensino e aprendizagem no Pibid geografia UFRN - Elisabeth Cristina Dantas de Araújo; Adriano Lima Troleis (Confins)
The educational resources used in the school environment are very important tools in improving the teaching and learning process, while contributing as a mediator between the teacher, the student and knowledge in a particular area. In the teaching of Geography, the use of these resources can be widely used in order to enrich the theoretical discussions and serve as a support for teaching practices, allowing the everyday experiences of students to gain meaning, facilitating their understanding of the relevant contents of geographical science. Thus, this paper proposes a discussion on the outcome of practices developed and observed by students of the Programa Institucional de Bolsa de Iniciação à Docência (PIBID) Geography UFRN, at partner schools, ranging from the development of educational resources to its implementation . The main objective of the program is the development of pedagogical strategies that enable the construction of academic learning of geography combined with conceptions of psychological theories Socio interactionist and Socio Constructivist, postulated by the theorists Vygotsky and Piaget, comprising learning as an everyday process that can be facilitated through the construction and use of teaching resources.